2018
DOI: 10.7717/peerj.4253
|View full text |Cite
|
Sign up to set email alerts
|

A streptomycin resistance marker inH. parasuisbased on site-directed mutations inrpsLgene to perform unmarked in-frame mutations and to verify natural transformation

Abstract: Haemophilus parasuis is a member of the family Pasteurellaceae and a major causative agent of Glässer’s disease. This bacterium is normally a benign swine commensal but may become a deadly pathogen upon penetration into multiple tissues, contributing to severe lesions in swine. We have established a successive natural transformation-based markerless mutation system in this species. However, the two-step mutation system requires screening of natural competent cells, and cannot delete genes which regulate natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Comparable variation has also been found in Glaesserella parasuis (G. parasuis), a naturally transformable, gram-negative, pleomorphic bacterium of the Pasteurellaceae group (Bigas et al, 2005;Dai et al, 2021). Although a comparison of the entire genome sequence of G. parasuis isolates published in NCBI showed that all strains contained the identified homologous genes required for natural transformation, such as pilA, comEA, comM, etc., many G. parasuis isolates are non-transformable (Dai et al, 2016(Dai et al, , 2018b. The molecular mechanism of such diversity is unclear, however, it may due to significant differences in the regulatory systems of the different strains.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable variation has also been found in Glaesserella parasuis (G. parasuis), a naturally transformable, gram-negative, pleomorphic bacterium of the Pasteurellaceae group (Bigas et al, 2005;Dai et al, 2021). Although a comparison of the entire genome sequence of G. parasuis isolates published in NCBI showed that all strains contained the identified homologous genes required for natural transformation, such as pilA, comEA, comM, etc., many G. parasuis isolates are non-transformable (Dai et al, 2016(Dai et al, , 2018b. The molecular mechanism of such diversity is unclear, however, it may due to significant differences in the regulatory systems of the different strains.…”
Section: Introductionmentioning
confidence: 99%